(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
This article addresses a survey carried out in a vocational education institution regarding the individual performance appraisal processes of employees in its commercial sector. The objective is to describe the current process and propose an improved alternative process, based on the identified limitations. The research was qualitative in nature and employed observation, questionnaire and document analysis as means of data collection. It was observed that the company was inflexible in its evaluation processes, summarily dismissing employees who did not reach their goals in a short period of time, generating turnover and costs. Additionally, certain basic aspects of performance appraisal such as feedback and transparency were ignored. It was found that with minor modifications, the current model could, without losing its characteristics, better balance the evaluation of the individual performance and the development of the people who make up the body of the organization.